Edukasi Bahaya Merokok pada Anak Sekolah Dasar Negeri 36 Tonasa Parappa Desa Laguruda - Jamal, Hudriani; Mahmudah Dulla, Arif Atul (Universitas Patria Artha, 2025)
Smoking is one of the risk behaviors that can reduce individual health quality, particularly among children and adolescents. This community service activity aims to improve students’ knowledge and attitudes through education about the dangers of smoking, enabling them to avoid smoking behavior as an effort to maintain health and prevent smoking-related diseases. The community service was conducted at Sekolah Dasar Negeri 36 Tonasa Parappa, Laguruda Village, Sanrobone Subdistrict, Takalar Regency. Educational activities on the dangers of smoking were provided to students to deliver accurate information regarding the definition of cigarettes, types of cigarettes, categories of active and passive smokers, harmful substances contained in a cigarette, the health risks and impacts of smoking, the dangers of passive smoking, smoke-free areas, and strategies to quit smoking. The educational media used combined PowerPoint slides and a projector to present the material visually and engagingly. A discussion and question–answer session followed to encourage active participation from the students. This activity is expected to foster good knowledge, attitudes, and behaviors from an early age to prevent the emergence of new smokers, promote health, and reduce smoking-related diseases.